Membangun SDM Unggul pada UMKM Lokal Sebagai Pilar Ekonomi di Kelurahan Kelapa Indah Kota Tangerang - Erwin Wijaya; Halimahtun Sa’diyah; Liana Fadilah; Martono Martono (Jurnal PKM Manajemen Bisnis, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in supporting regional economic growth and creating employment opportunities. However, many local culinary MSMEs still face challenges related to human resource quality, managerial capability, and business competitiveness. Therefore, strengthening human resources is essential to improve the sustainability and performance of MSMEs. This Community Service Program (PKM) aimed to enhance the knowledge and competencies of local culinary MSME owners in Kelapa Indah Village, Tangerang City, enabling them to become more competitive and contribute to local economic development. The program was conducted on June 7, 2026, in Kelapa Indah Village, Tangerang City, and was implemented by five lecturers and graduate students from the Master of Management Program, Universitas Pamulang. The participants consisted of 25 local culinary MSME owners. The implementation methods included presentations, practical sessions, discussions, and question-and-answer activities. The PKM was carried out through three stages: preparation, implementation, and reporting. The results indicated that participants demonstrated increased understanding of human resource development, business management, and entrepreneurial strategies. The interactive learning approach encouraged active participation, knowledge sharing, and practical problem-solving. Overall, the program successfully strengthened participants' managerial awareness and competencies, supporting the development of high-quality human resources as a fundamental pillar for improving the competitiveness and sustainability of local MSMEs in Kelapa Indah Village.